Beginning PL/SQL From Novice to Professional - Bales, Donald J.; SpringerLink (Online service) (Berkeley, CA : Apress, 2007)
Get started with PL/SQL, the built-in language that every Oracle developer and database administrator must know, in Beginning PL/SQL, a fast-paced and example-filled tutorial. Learn from author Don Bales extensive experience to discover the most commonly used aspects of PL/SQL, without wasting time with obscure and obsolete features. Bales takes his 20+ years of experience and a wealth of statistics he's gathered on PL/SQL usage over those years and applies the 80/20 rule: cover what's most needed and used by PL/SQL professionals and avoid what's not necessary! The result is a book that covers all the key features of PL/SQL without wasting your time discussing esoteric and obsolete parts of the language. Learn what really matters, so that you can get to work feeling confident with what you know about PL/SQL. Discover the 20% of PL/SQL that gives you 80% of the bang! Key topics covered include variables and datatypes, executing statements, working with cursors, real-world objects, debugging, testing, and more. Learn how to write production-level, object-oriented PL/SQL. You'll explore relational PL/SQL, but unlike most other books on the subject, this one emphasizes the use of PL/SQLs object-oriented features as well. Work through real examples of using of PL/SQL. You'll learn PL/SQL by applying it to real-world business problems, not by heavy theory.
Genesis -- PL/SQL Is Square, Man! -- Now Where Did I Put That? -- Whoa! One Statement at a Time, Please! -- Next Please, One Row at a Time! -- Just Like It Is in the Real World! -- So Just What$1 (Bs Happening Here? -- Test, Test, Test, and Test Again -- What Does This Thing Do Anyway? -- Fairy Tales.s
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books